COMPARATIVE RESEARCH ON THE DESTRUCTIVE BENDING MOMENTS OF SOME CORNER JOINTS OF FRAME STRUCTURAL ELEMENTS MADE OF SOLID SPRUCE WOOD WITH A CROSS SECTION OF 50 X 30 MM PART III: END CORNER MORTISE AND TENON JOINTS - Kyuchukov, Georgi; Kyuchukov, Borislav; Jivkov, Vassil; Marinova, Assia; Gruevski, G; Kalapotliev, Z (Innovation in Woodworking Industry and Engineering design, 2016)
The results from the research on the destructive bending moments of the end corner mortise and tenon joints of structural elements made of solid spruce wood with a cross section of 50 x 30 mm are given whereas these joints are used mainly in the construction of sitting furniture, tables and beds.It was established that the type of joints has significant influence on the destructive bending moment. This is defined by the type and size of joint elements and the area of the contact sur-faces of the joints.The following joints are destroyed at a considerably big bending moment: Haunched blind mortise and tenon joint; Blind twin mortise and tenon joint; Blind mortise and tenon joint Haunched through twin mortise and tenon joint; Haunched through mortise and tenon joint; Haunched blind twin mortise and tenon joint; Twin through mortise and tenon joint; Through mortise and tenon joint.It is recommended that the research results are taken into consideration in strength design of furniture.